Revitalizing Sustainability: Exploring the Feasibility and Impacts of Polymer Waste Buy-Back Programs in Nigeria - Solaja, Oludele Mayowa; Onafeso, Olumide D.; Amoo, Olamide Faruq (CV. Literasi Indonesia, 2024)
The escalating environmental concerns associated with polymer waste have prompted a global call for sustainable solutions. This study explores the viability and potential impact of implementing buy-back programs for polymer waste in Nigeria. Through an extensive review of existing literature, environmental policies, and case studies, the research aims to provide insights into the economic, environmental, and social dimensions of such initiatives. The study adopted a qualitative research design with the use of in-depth interviews among 25 participants comprising ecopreneurs, environmental management officers, and community residents in the Ijebu region of Ogun State, Nigeria. Based on participant interviews, the research shows that stakeholders realize the economic and environmental benefits of such programs, but various difficulties must be overcome for success. Efficient collection and transportation methods are needed due to logistical challenges like those in waste management programs. Positive policies are needed to stimulate and regulate buy-back efforts, as is regulatory assistance. Community trust and engagement are crucial to buy-back program success.